Characterization of SAR Clutter and Its Applications to Land and Ocean Observations - Gao, Gui.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses statistical modeling of single- and multi-channel synthetic aperture radar (SAR) images and the applications of these newly developed models in land and ocean monitoring, such as target detection and terrain classification. It is a valuable reference for researchers and engineers interested in information processing of remote sensing, radar signal processing, and image interpretation.
Survey on Statistical Modeling of SAR Data -- Statistical Modeling of Single-Channel SAR Data -- Statistical Modeling of Multi-Channel SAR Data -- Target Detection and Terrain Classification using Single-Channel SAR Data -- Ship Detection in Multi-Polarimetric SAR Images -- Moving Vehicle Detection in Along-Track Interferometric SAR Complex Images -- Ship Detection in Along-Track Interferometric SAR complex Images.
Keywords: Signal processing; Geographic information systems; Mathematical models; Signal, Speech and Image Processing; Geographical Information System; Mathematical Modeling and Industrial Mathematics